Senior High School Students’ Experiences and Perceptions of Wordwall in Writing Descriptive Texts - Shofia Rafifatus Nadila; Ahmad Munir (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study explores senior high school students’ experiences and perceptions of using Wordwall, a gamified learning platform, in writing descriptive texts in an Indonesian EFL classroom. Many learners face challenges such as limited vocabulary, low motivation, and writing anxiety. To understand how students experience the use of Wordwall, a qualitative descriptive design with a phenomenological approach was employed. Data were collected through semi-structured interviews, focus group discussions, classroom observations, and analysis of student writing samples. Thematic analysis revealed that Wordwall helped students improve vocabulary, boost motivation, and reduce anxiety by offering engaging, interactive tasks like quizzes and instant feedback. Students described their learning process as more enjoyable and confidence-building. Despite minor technical issues, most participants found Wordwall beneficial in supporting their writing development. These findings highlight the value of gamified tools in enhancing student engagement and confidence in EFL writing classes. The study provides practical insights for educators seeking to integrate meaningful digital tools into language instruction.